The Presidency of George W. Bush - Greene, John Robert, 1955- (Book collections on Project MUSE., 2021)
"The presidency of George W. Bush is indelibly linked in the minds of Americans with the 9/11 terrorist attack on the World Trade Center and the subsequent War on Terror that transformed US foreign policy and the international political order. While John Robert Greene's history of Bush's presidency covers these events in detail, especially the wars in Afghanistan and Iraq, the book addresses the entirety of his time in office, including debates over executive power, the disaster of Hurricane Katrina, and the economic recession. Only the second time the son of a president became president himself, Bush 43's presidency remains highly controversial and the events of those years continue to shape geopolitics today, drawing both praise and censure from partisan commentators. Drawing on all available sources, Greene's account sheds fresh light on the first presidency of the twenty-first century in an effort to clear aside misunderstandings and deepen our understanding of those consequential years"--